Biological flora of New Zealand (15): Ixerba brexioides, tāwari. Issue 1 (2nd January 2018) - Nepia, Rachel E.; Clarkson, Bruce D.
ABSTRACT: This review summarises the biology and ecology of the distinctive North Island New Zealand endemic tree Ixerba brexioides (A.Cunn.). The genus Ixerba is monotypic and belongs to the family Strasburgeriaceae found only in New Zealand and New Caledonia. Ixerba brexioides (tāwari) is a New Zealand tree restricted to rain forests north of 39°S latitude in areas of mature soil in mild, moist climates. With conspicuous white flowers displayed en masse between November and January each year and dark green, long and toothed leaves arranged in whorls, it has earned recognition as one of New Zealand's most attractive trees. Inflorescences are predominantly insect pollinated, with occasional bird visitation. Capsular fruit are produced in early autumn and dehisce to reveal dark black-purple seeds with an orange fleshy aril that are bird dispersed. Seeds germinate quickly, without a dormancy period, most commonly on soil, logs and mounds, but grow slowly (1.6–2.4 mm year diameter growth rate) in shade conditions until canopy gaps open. Chemicals associated with its leaves include ursolic acid and proanthocyanidins, but their significance is unknown. Agglomerative hierarchical cluster analysis defined four main forest types dominated by I. brexioides centred on Northland, Waikato, Coromandel and Urewera, the floristically richest occurring in Northland. The genus first appeared in the fossil record in New Zealand in the late Eocene. Flowers of I. brexioides (whākou) were historically used by Māori in garlands and necklaces, while peak flowering was a signal to harvest certain crops. Ixerba brexioides honey is popular and honey crops are sought after in areas where the trees are abundant and accessible to beekeepers. Though not currently threatened, the distinctive and geographically limited I. brexioides is one of the many New Zealand trees requiring additional research. Priorities include potential threats of climate change, susceptibility to inbreeding depression and the role of birds as dispersers.